Towards Indonesian Cloud Campus - Taqwan Thamrin; Iing Lukman; Dina Ika Wahyuningsih (Bandar Lampung University (UBL), 2013)
Nowadays, Cloud Computing is most discussed term in business and academic environment.Cloud campus has many benefits such as accessing the file storages, e-mails, databases,educational resources, research applications and tools anywhere for faculty, administrators,staff, students and other users in university, on demand. Furthermore, cloud campus reduces universitiesâ IT complexity and cost.This paper discuss the implementation of Indonesian cloud campus and various opportunies and benefits of cloud services for universities. And suggested cloud infrastructure prototypetowards cloud campus